2018
DOI: 10.1002/eat.22820
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for disordered weight control behaviors among Korean adolescents: Multilevel analysis of the Korea Youth Risk Behavior Survey

Abstract: The findings suggest that DWCB are prevalent among Korean adolescents across age, sex, and socioeconomic status. Social contextual factors including school and familial environmental factors, as well as individual characteristics, should be considered when developing effective prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 65 publications
0
26
0
5
Order By: Relevance
“…We built the aforementioned models stratified by gender based on the marginally significant interaction between gender and weight perception pattern in our sample (p = 0.07), and further performed subgroup analysis across BMI category (normal and obese). Additionally, given the rapid change in social norms regarding body image in South Korea over the past decades [ 12 , 23 , 24 ], we performed stratified analysis across younger (i.e., aged 19–40 years) and older (i.e., aged 41–65 years) aged groups. For all multilevel modeling, we used MLwiN 3.01 (Center for Multilevel Modeling, Bristol University) by adapting a Markov Chain Monte Carlo (MCMC) with Metropolis-Hastings algorithm with uninformative priors, a Bayesian approach implemented in MLwiN, and set the level of significance at 0.05 (two-sided) [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We built the aforementioned models stratified by gender based on the marginally significant interaction between gender and weight perception pattern in our sample (p = 0.07), and further performed subgroup analysis across BMI category (normal and obese). Additionally, given the rapid change in social norms regarding body image in South Korea over the past decades [ 12 , 23 , 24 ], we performed stratified analysis across younger (i.e., aged 19–40 years) and older (i.e., aged 41–65 years) aged groups. For all multilevel modeling, we used MLwiN 3.01 (Center for Multilevel Modeling, Bristol University) by adapting a Markov Chain Monte Carlo (MCMC) with Metropolis-Hastings algorithm with uninformative priors, a Bayesian approach implemented in MLwiN, and set the level of significance at 0.05 (two-sided) [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…Traditional Korean society associated a moderately “plump body” with positive values (e.g., beauty and wealth), but a “thin body” with negative images (e.g., illness and poverty) [ 12 , 22 ]. However, the rapid social changes characterized by industrialization, urbanization, and Westernization over the past half-century in South Korea have flipped the traditional norms and values regarding body image [ 12 , 23 , 24 ]. As a result, the thin-ideal is prevalent in South Korea, and having a slim body is viewed as an essential component for a successful marriage and career, particularly among Korean women [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of our participants lived in a small or medium-sized city or in the rural areas of a large city, which could partly explain our findings since mean ChEAT scores have been observed to be higher in large cities than in small and medium-sized cities, possibly due to susceptibility to more social pressure and to emphasized media influence in larger cities [31]. It has been suggested that socioeconomic status affects the prevalence of DES [56,57], which might explain low mean scores in our study. However, information on parental SES was not available here.…”
Section: Discussionmentioning
confidence: 70%
“…Çalışmamızla benzer şekilde Güney Kore'de son yıllarda yaşanan hızlı sosyal değişimlerin toplumun vücut imajına bakış açısını değiştirdiği ince bir vücut yapısına sahip olmanın başarılı bir kariyer için gerekli olduğuna inanıldığı belirtilmektedir. [32] İnce bir vücuda sahip olmak isteyen ve vücut ağırlığından memnun olmayan kızların yüzdesi ülkemizde oldukça fazladır ve bu sonuç gelişmiş ülkelerdekilere yakındır. [33] Ayrıca diyet gruplarında beden imgesi, benlik algısı ve vücut kitle indeksi arasındaki ilişkinin yeme bozukluklarının psikopatolojisini anlamamıza yardımcı olabileceği belirtilmiştir.…”
Section: Discussionunclassified